Le blason populaire au Québec, un phénomène révolu ? - Dugas, Jean-Yves (Ethnologies, 1984)
AbstractSince the early Sixties with the Révolution tranquille, the Province of Québec lives an important identification crisis among its population. A prodigious expansion of gentilices (names of habitants) may be observed and in a same way the preservation of many nicknames. After the examination of nickname notion definited as the collective amusing, mocking or satirical designation of the people living in some places, we try to establish a thematic typology for this kind of appellations. The most important themes concern animais, food, clothes, religion and human being (physical and moral characteristics ; work ; riches orpoverty ; language ; leisures) and establish on 349 denominations listed and annexed. If the modem life circumstances stop nicknames evolution phenomenon, they stay well-known in campaigns particularly. Maybe Quebecers are ready to imagine a new identified mode.